Income Inequality and City Size - Long, James E.; Rasmussen, David W.; Haworth, Charles T. (The Review of Economics and Statistics, 1977)
The distribution of income in the urban context has received relatively little attention from economists. Limited information has been employed to assert an inverse relationship between city size and income inequality (Duncan and Reiss, 1956; Richardson, 1973). This relationship can be rationalized by the fact that both city size and inequality are related to the level of income. Kuznets (1955) hypothesized a negative relationship between income and inequality, and he is supported by the findings of Aigner and Heins (1967), Conlisk (1967), and Al-Samarrie and Miller (1967) using state data and by Frech and Burns (1971) using SMSA data. Sveikauskas (1975) has documented that incomes are higher in larger cities. In this paper we analyze the relationship between city size and income inequality. After controlling for other factors that influence income inequality by using regression analysis on cross section data for 79 U.S. metropolitan areas, we find that income inequality appears to increase with city size.